Safe and non-toxic hydroxyalkylation of xylan using propylene carbonate. (April 2016) - Akil, Youssef; Lorenz, Dominic; Lehnen, Ralph; Saake, Bodo
Graphical abstract: Highlights: Substitution of hazardous epoxide with green chemical propylene carbonate. Hydroxyalkylation of different xylans achieved in a wide range of DS and MS. Arabinoxylan showed higher reactivity compared to glucuronoxylan. Increasing water solubility was obtained for higher substitution values. Abstract: Xylan is an abundant polysaccharide consisting of xylose units and has gained a significant increase in research interest in the last decades. Hydroxyalkylation of xylan is a way of modifying xylans to achieve xylan ethers with better water solubility as well as to form materials which can be used for gels, films or packaging applications. In this work, hydroxyalkylation is performed with non-toxic propylene carbonate in dimethyl sulfoxide (DMSO) with alkaline 1, 8-Diazabicyclo [5.4.0]undec-7-ene (DBU) as catalyst. In this way highly toxic and explosive, but currently widely used propylene oxide can be avoided. A decarboxylation step is taking place during the reaction, making the product identical to the one, which can be obtained by using epoxides. The obtained products show degrees of substitution between 0.1 and 1.5 with low tendencies for homopolymerization along the side chain. Therefore the procedure allows the tailored production of xylan ethers via hydroxyalkylation. The products are characterized by one- and two-dimensional NMR- as well as FTIR-spectroscopy, mass spectrometry, SEC and regarding their water solubility.